Patrimônio cultural e acessibilidade das pessoas com deficiência no Museu das Bandeiras (MUBAN) – Cidade de Goiás - Morais, Kenia Aparecida de (2021)
The research presented here discusses the cultural inclusion of people with disabilities in the Museu das Bandeiras space in Goias City. From the analysis of two spheres: the museum space, and the person with disabilities, we proposed some heritage education actions that can facilitate this process. The methodology used in the research sought, through interviews, bibliographic, documentary and iconographic analysis, to know the relationship of the museum to the person with disabilities and the relationship of this public to the museum, establishing the main specificities of inclusion in this path. The results allowed us to know the main challenges of the Museum of Flags when identifying and serving the public with disabilities and presenting actions that can be implemented in the educational plan of the institution. As a final product of the research, we presented to the museum the proposal for a temporary exhibition entitled “The museum and the senses” in which visitors are invited to think about these subjects beyond these boundaries of structural mobility, which allow the person with disabilities an accessibility to representations of cultural heritage present in this institution.